Uso de pastas dentales en niños menores de 12 años en el Perú durante los años 2019-2021: un análisis multivariado - Carrizales, Leonid (2024)
Background: Oral hygiene with fluoride toothpaste is an effective method to prevent dental caries in children, however, this measure could have been affected in recent years by various factors. Objective: To determine the use of toothpaste in Peruvian children under 12 years of age in the period 2019-2021. Materials and methods: Cross-sectional study where registers of the Demographic and Family Health Survey - ENDES (from 2019 to 2021) were obtained, collecting information on oral health. The results were examined according to the study variables and statistical analysis was performed. Results: 98,89% (n=81668) of Peruvian children under 12 years used toothpaste in the period 2019-2021, however, its use ceased over the years, finding a statistically significant differences. The use of fluoridated toothpaste with a minimum of 1000 ppm increased over the years, obtaining a statistically significant difference. In the multivariate analysis, there was a positive association between the year 2020 and the use of fluoridated toothpaste with a minimum of 1000 ppm (aPR=1,04; 95% CI=1,01-1,07 and p=0,004). A positive association was also found between the year 2021 and the use of fluoride toothpaste with a minimum of 1000 ppm (aPR=1,12; 95% CI=1,10-1,15 and p<0,001). Conclusions: There is an association between the use of toothpaste and year, natural region, area of ​​residence, place of residence, altitude and age; also, between the use of fluorinated toothpaste with minimum 1000 ppm and year, natural region, area of ​​residence, place of residence, wealth index and age.